Determinação dos metais chumbo, cádmio, níquel e cromo em massa de modelar (slime) - Flora, Rosiane Ariane da Silva (2021)
Plasticine (SLIME) became so popular among children that it became a sensation. For weeks, the videos explaining recipes were the most accessed on Youtube. Also known as amoeba, jelly, slime brings a fun that can pose great risks for children. In its composition, the recipe has components such as boric acid (or boricada water), a substance which has high toxicity. Its use is not regulated by the National Health Surveillance Agency and can be harmful to health, especially for children. In 2002, ANVISA banned a toy called Mad Goo because of the presence of borax. As it is a chemical product, even in doses recommended by the competent authorities, it should not be handled by children as it poses a high risk. In addition to boric acid, slime may have metals in its composition. In this context, a study was carried out to identify the presence of heavy metals lead, cadmium, nickel and chromium, from 12 samples acquired in the Campo Mourão/PR business and submitted to analysis by Atomic Absorption Spectroscopy (EAA). The inspection agency, INMETRO, stipulates maximum element migration limits in mg kg-1 from the toy material modeling clay and paint to with your fingers. According to this limit, it was possible to identify the presence of lead and nickel in all analyzes samples. The analyzes showed that the metals presented concentrations ranging from 0.55 to 1.73 mg Kg-1 for lead and 2.62 to 17.51 mg Kg-1 for nickel. Cadmium and chromium metals were not detected in the samples.